SABERES DOS COCAIS MARANHENSES: dialogicidade com mulheres Quilombolas Quebradeiras de coco babaçu de Laranjeiras - SILVA, Tercilia Mária da Cruz (2023)
This study problematizes the possibilities of conceiving dialogue with the daily knowledge of women Quilombolas Quebradeiras de coco babaçu, aiming at practices of dialogic literacy. It analyzes the Freirian concept of dialogicity, based on two pieces of knowledge from the daily lives of women Quilombolas Quebradeiras de coco babaçu, aiming at the elaboration of educational practices of dialogic literacy. The locus of the investigation is the quilombola community of Laranjeiras (CQL), located in the rural area of the municipality of Aldeias Altas – Maranhão. It has a suleada approach with a principle of equity that problematizes the formulation and institution of a hegemonic knowledge, with an epistemic stance, that disqualifies many other types of knowledge. It is supported by theoretical and methodological bases against hegemonic, by means of the deepening of the concept of dialogicity (FREIRE, 1979, 1989, 1996, 2011, 2015, 2019) in the composition of the knowledge of the women Quebradeiras de coco babaçu. It aims to acquire this knowledge, understand ways of creation its dialogicity and identify its possibilities of use in educational practices of dialogic literacy. It uses the dialogicities of Paulo Freire (1989; 2011), complemented by the studies of Mikhail Bakhtin (2006) and the local knowledge of Paulino Castiano (2016), both articulated as contributions to colonial perspectives (GROSFOGUEL, 2010, 2016; GONZALEZ, 2011; QUIJANO, 2005) and Afro-centered (ASANTE, 2009; 2016; MAZAMA, 2009; Oyěwùmí, 2021). The methodological bases seek inspiration in elements of Geertz's interpretive ethnography (2008) and in the creative and artistic recommendations of Sociopoetics developed by Jacques Gauthier (2004; 2012; 2015). It confirms the knowledge of women Quebradeiras de coco babaçu, in a dialogic context, provokes discussions around the legitimacy of the use of African knowledge and knowledge in the educational practices of dialogic literacy and supports the potential of dialogicity as a delineator of the process founded with the African civilizational values, present in Quilombola community of Laranjeiras and that derived origins from the generating themes; afro-knowledge e confetos of the community women.